STRESS AND INTERNATIONAL ENTREPRENEURHSIP: The dark side of international entrepreneurship - Pak, Yekaterina (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
Entrepreneurship attracts people with high job satisfaction and financial independence. Unfortunately, being deceived by this image, people do not pay attention to side effects of entrepreneurship. This ignorance usually turns into devastating results for entrepreneur’s health and venture performance. Therefore, it is required to seek ways to avoid these situations. The interest of the study lies in understanding of stress influence on international entrepreneurs by considering stress as a negative side effect of international entrepreneurship. To cover the concept of entrepreneurial stress completely, the study was divided into three section presented by following research questions: 1. What are the antecedents of entrepreneurial stress? 2. What are the consequences of entrepreneurial stress? 3. What coping strategies are applied to address entrepreneurial stress? Systematic literature review has been chosen as scientific approach to answer above questions due to the reason that it enables to minimise inconsistencies of both concepts of international entrepreneurship and stress. This method has afforded an opportunity to distinguish such stress causes as role conflict, overload, and ambiguity. Additionally, the study has covered the notion of stress moderators. The author argues that entrepreneurial traits, venture environment, and social support can have influence on degree of stress perception. Further, it has been proven that unaddressed stress could lead to reduction of entrepreneur’s psychological and physiological health. It should be taken into consideration that degree of both job satisfaction and performance would depend on the level of perceived stress. The last part of study emphasises the coping strategies. The author argues that it is important for an international entrepreneur to comprehend his or her and others’ emotions in order to overcome negative consequences of stress. In addition, the author suggests that an international entrepreneur needs to practise job sharing to reduce the amount of work to be completed. Moreover, it is believed that job sharing can help to overcome work-family conflict that prevails among entrepreneurs. The author anticipates that results of study can be beneficial for entrepreneurs who aim to achieve great results.